Determining the Relationship Between Nurses' Attitudes to Professional Autonomy and Job Satisfaction - Seda Şahan; Cevriye Özdemir (Galenos Publishing House, 2023)
Objective:In this study we aimed the determine nurses' attitudes toward professional autonomy and the relationship between job satisfaction.Method:This study was conducted with 302 nurses between December 2022 and March 2023. The following two tools were used for data collection: Attitudes towards professional autonomy scale for nurses and job satisfaction scales for nurses. The research data was used to collect the numerical and percentile distribution, Kruskal-Wallis-H, and correlation analyses were used to analyze the data.Results:According to this study it was found that the total mean score of the nurses obtained from the attitude scale toward professional autonomy was 69.07±4.63. The total mean score of the nurses obtained from the job satisfaction scale was found to be 22.27±3.81. It was found that there was a positive and significant correlation between the attitude towards professional autonomy total scale score and the job satisfaction scale total score (r=0.384, p=0.044).Conclusion:It was determined that the nurses' attitudes towards professional autonomy and job satisfaction were above avarage. It has been determined that there is a significant relationship between the attitude toward professional autonomy and job satisfaction; as the attitude toward autonomy increases, job satisfaction increases.